Changes of the growth plate in children: 3-dimensional magnetic resonance imaging analysis - Hyung Ho Yun; Hyun-Jung Kim; Min-Sun Jeong; Yun-Sun Choi; Ji-Young Seo (Korean Pediatric Society, 2018)
Purpose This pilot study assessed changes in the growth plate and growth rates in children during a 6-month period. Methods The study included 31 healthy children (17 boys, 14 girls) under evaluation for growth retardation. Height, weight, bone age, insulin like growth factor-1 (IGF-1), and insulin like growth factor binding protein 3 (IGF-BP3) were measured at baseline and after 6 months. In addition, the diameter, thickness, and volume of the femoral and tibial growth plates were measured using magnetic resonance imaging. Results The mean bone age in boys and girls was 11.7 and 10.7 years, respectively. In boys, height (z score) (-0.2 vs. 0.0), weight (z score) (0.8 vs. 1.1), body mass index (BMI) (z score) (1.27 vs. 1.5), IGF-1 (ng/mL) (343.6 vs. 501.8), and IGF-BP3 (ng/mL) (5,088.5 vs. 5,620.0) were significantly higher after 6 months. In girls, height (z score) (-1.0 vs. -0.7), weight (z score) (-0.5 vs. 0.1), BMI (z score) (-0.02 vs. 0.3), IGF-1 (ng/mL) (329.3 vs. 524.6), and IGF-BP3 (ng/mL) (4,644.4 vs. 5,593.6) were also significantly higher after 6 months. In both sexes, the mean diameter and volume of the femoral and tibial growth plates were significantly increased 6 months later. Conclusion No significant correlation was found between changes in the growth plate and clinical parameters in children with growth retardation in this study, other than correlations of change in femoral diameter with weight and BMI. A larger, long-term study is needed to precisely evaluate the correlation between change in the growth plate and growth.